Modern Aspects of The Use of Osteoplastic Materials in Dentistry (Eurasian Medical Research Periodical, 2024)
Current trends in the use of osteoplastic substances in dental practice emphasise the importance of restoring bone structure after inflammatory processes, trauma and surgical interventions associated with tooth extraction, which often results in a lack of bone tissue. Natural regeneration rarely provides sufficient new bone volume, which complicates the implantation process.